Corrosion inhibition of carbon steel in 0.5 M NaCl aqueous solution by humid air plasma treatment - Addou, Ahmed; Ghali, Noureddine; Mutel, Brigitte; Benstaali, Baghdad; Bentiss, Fouad; Brisset, Jean-Louis (The European Physical Journal-Applied Physics, 2013)
Carbon steel (C75) is exposed to highly reactive species such as hydroxyl radicals · OH created by a gliding arc discharge (GAD) in humid air at atmospheric pressure. The protective properties of carbon steel treated by GAD are studied versus different treatment times ( t ) and for an immersion in corroding 0.5 M sodium chloride solution during 24 h. Evolutions of corrosion rate are studied using weight loss measurements and electrochemical methods, e.g., electrochemical impedance spectroscopy (EIS) and potentiodynamic polarization. The results obtained by GAD treatment show that the corrosion rate of steel decreases with the ennoblement of the corrosion potential and the decrease of the corrosion current density. This indicates that the plasma treatment acts as an anodic type inhibitor and suggests the formation of a protective layer. EIS measurements confirm the presence of this film: the charge transfer resistance ( R ct ) increases with GAD treatment time, leading to a corrosion inhibition efficiency around 73% for a treatment time equal to 60 min. This confirms the importance of the plasma effect. The gliding arc discharge is a clean and efficient technology for the surface treatment of carbon steel; it improves the anticorrosion properties of steel in aggressive environments, forming a resistant and insulating barrier.